Pengaruh Jenis Pupuk dan Tingkat Arbuskular Mikoriza terhadap Pertumbuhan dan Hasil Jahe (Zingiber officinale) - Dhimas Taufika Putra; Samanhudi Samanhudi; Purwanto Purwanto (Universitas Sebelas Maret, 2014)
Ginger (Zingiber officinale) is one kind of plants to be processed as traditional medicine, drinks, and spices. the smallest type of ginger that has many benefits as medical plant. Demand for ginger plants growing in the community is increasing. Additions of manure and arbuscular mychorrhizal fungi (AMF) can increase the quality and quantity of ginger. This was conducted to obtain the kinds of manure and levels of AMF to ginger to produce optimum growth and yield. This research used a completely randomized design (CRD) consisting of two treatment factors, namely planting medium and arbuscular mycorrhizal fungi (AMF). Results were analyzed by analysis of variance and if there is a real difference continued DMRT 5% level. The results showed that the differences in the kinds of manure and the levels of AMF increase growth and yield of ginger. Chicken manure application showed the highest results in the fresh weight of stover plant, dry weight of plant stover, fresh weight of plant rhizomes, and dry weight of the rhizomes. Whereas the additions of AMF 15 grams per plant in zeolite showed the highest results in the number of plant tillers, dry weight of plant stover, fresh weight of plant rhizomes, and dry weight of the rhizomes.